Photoresponse in Ge/Si nanostructures with quantum dots - Nikolenko, A.S.; Kondratenko, S.V.; Vakulenko, O.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2006)
Photovoltaic properties of Si samples with Ge quantum dots were studied. Photosensitivity spectra and current-voltage characteristics at 90 and 290 K were investigated. Negative photoconductivity of samples was revealed in the spectral range of 0.6 to 1.1 eV. Irregular temperature dependence of photo-emf in the temperature interval from 100 to 250 K was measured and analyzed.